2020
DOI: 10.3390/ijms21020566
|View full text |Cite
|
Sign up to set email alerts
|

Deimination and Peptidylarginine Deiminases in Skin Physiology and Diseases

Abstract: Deimination, also known as citrullination, corresponds to the conversion of the amino acid arginine, within a peptide sequence, into the non-standard amino acid citrulline. This post-translational modification is catalyzed by a family of calcium-dependent enzymes called peptidylarginine deiminases (PADs). Deimination is implicated in a growing number of physiological processes (innate and adaptive immunity, gene regulation, embryonic development, etc.) and concerns several human diseases (rheumatoid arthritis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 71 publications
(118 reference statements)
1
63
0
Order By: Relevance
“…Furthermore, SGL 07 and SGL 19 lysates induced the keratinocyte expression of protein-arginine deiminase type-1 (PADI1), 7.22-fold and 4.58-fold respectively. PADI1, immunodetected in all the neo-epidermis, catalyzes the conversion of protein-bound arginines into citrullines, a deimination process which involves clot proteins and that is fundamental for the wound closure 46,47 . The results of migration assays indicated that the L. plantarum SGL 07 and L. salivarius SGL 19 lysates accelerate the wound closure likely by enhancing the movement of keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SGL 07 and SGL 19 lysates induced the keratinocyte expression of protein-arginine deiminase type-1 (PADI1), 7.22-fold and 4.58-fold respectively. PADI1, immunodetected in all the neo-epidermis, catalyzes the conversion of protein-bound arginines into citrullines, a deimination process which involves clot proteins and that is fundamental for the wound closure 46,47 . The results of migration assays indicated that the L. plantarum SGL 07 and L. salivarius SGL 19 lysates accelerate the wound closure likely by enhancing the movement of keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium is a key modulator in a range of immunological, metabolic and developmental functions [199][200][201][202]. Calcium signalling is linked to a wide range of physiological and pathological processes [203][204][205], is a key driver for post-translational deimination [206][207][208] and plays an important role in the regulation of EVs [11,48]. In cattle, calcium is linked to many immunological pathways including inflammatory diseases [209], virus replication [210], parasitic infection [211], wound healing [212], reproduction [213,214] and adrenal function [215].…”
Section: Discussionmentioning
confidence: 99%
“…PADs and associated protein deimination are crucial players in cancer and autoimmune and neurodegenerative diseases (17,19,20,22,25). PADs have received particular attention due to roles in cancer (20,22,26,27), rheumatoid arthritis (28)(29)(30)(31)(32)(33), multiple sclerosis (34)(35)(36)(37)(38), as well as due to their contribution to skin physiology and diseases (39). PADs have furthermore been shown to play crucial roles in hypoxia and CNS regeneration (40)(41)(42)(43)(44), and roles for PAD2 in promotion of oligodendrocyte differentiation and myelination have been shown (45).…”
Section: Introductionmentioning
confidence: 99%